LOCAL GOVERNMENT ADMINISTRATION: THE STATE GOVERNORS AND DEFICIT OF DEMOCRACY IN GRASSROOTS NIGERIA (UCC Law Journal, 2023)
After twenty-three years of the fourth democratic republic in Nigeria, there is a strong temptation to presume that democracy has taken firm roots at the grassroots. However, the whimsical manner by which the state Governors have subverted and hijacked the Local Governments (LGs) structures in their respective states suggests the contrary. The 1999 Constitution of the Federal Republic of Nigeria (as amended) makes provisions for elected LG Councils, yet, the Governors having being in firm charge have rendered these provisions illusory. They toy with the autonomy and vitality of the LGs, interfering and removing elected LG officials at their fancies. This study assesses the role of the state Governors in the determination of representations at the LG level in Nigeria and its effects in providing credible leadership for rural development. Data were gathered through primary and secondary sources such as 1999 Constitution of the Federal Republic of Nigeria (as amended), books relevant to the present study, peer review journal articles, judicial precedents, internet materials and newspaper reports. The above data were subject to content analysis. The paper finds that the LG elections in Nigeria are not given premium position by many state governments which robs the nation of a structured leadership development avenue. It also finds that the Electoral Management Body in the states are not independent. The paper, therefore, proffers Constitutional reforms as the way out of the wood. This will not only stop the Governors from acting capriciously and as omnipotent emperors, it will also allow the LGs enhance their capacity for optimum utilization of local initiatives through democratic means.